Real-time vessel and oil spill detection in the Argentine ocean littoral using SAR satellite imagery - Delrieux, Claudio Augusto (2016)
Oil-spill and furtive vessel detection are among the most required real-time monitoring tasks for environmental and government authorities. In Argentina, whose sea jurisdiction is huge (about one million square km), human asisted monitoring is unfeasible, and therefore remote sensing technologies, for instance satellite imagery, is the only operative and economically feasible solution. Recent associated efforts between the National Aerospace Activities Council of Argentina (CONAE) and its Italian counterpart to operate together the SAOCOM and COSMO satellite constellations enabled the possibility of developing a system capable of providing accurate, realtime space-born SAR imagery. In this work, we describe the theoretical foundations and implementation details of AMTO (Ambiente de Monitoreo TerrestreOceanico) ´ , a system specifically designed to take advantage of the SAR imagery delivered by those two satellite constellations, to provide real-time detection of vessels and oil spills.